زكاة الفطر: معاني ودلالات وأحكام: Zakat Al-Fitr: Meanings, Indications and Provisions - Murshed, Amer Abdulwahab Mahyoub; Abdo Amer, Eftekhar Ali (Online Journal of Research in Islamic Studies, 2019)
The Fuqaha have agreed on the obligation of zakat Al-Fitr on the one who has food and supplies for the day of Eid and its night, and its obligatory for every Muslim big or small, male or female, free or slave, healthy or sick and rich or poor. The research aims at showing the obligation of Zakat Al-Fitr to Muslims and what is required of a Muslim if delayed in the output of Zakat and showing how to give Zakat taking into account what the poor person needs in his country. The methodology I followed in the research is a descriptive analytical method. The research concludes that Zakat Al-Fitr has great values and outcomes, which are: completing the fast of the Muslim, purification of the heart of a fasting person, comforting and enriching the poor and the exclusion of them from the question and the need on the day of Eid. Zakat Al-Fitr is considered an important way of strengthening ties and spreading love, domesticity and familiarity in Islamic societies.